Evaluating score distributions in the revised Dutch version of the Childhood Health Assessment Questionnaire - Helders Paul JM; Takken Tim; van Pelt Philomine A; Ouwerkerk Jessika W; Net Janjaap (BMC, 2008)
Abstract Objectives Evaluating the original, and the revised version of the Dutch Childhood Health Assessment Questionnaire (CHAQ). To explore the effect of different score calculation methods and eight more challenging items as proposed by Lam et al. (2004) on the score distribution in a population of patients with Juvenile Idiopathic Arthritis (JIA). Methods Two convenience samples of 59 and 31 children with JIA were studied. Box-and-whisker plots and the Kolmogorov-Smirnov (K-S) one-sample test of normality were used, to explore the score distributions. Results The results of this study confirm a ceiling effect when using the original CHAQ-30 with either score calculation method. The original CHAQ with the added eight more challenging items and the "mean" score calculation method, as well as the revised CHAQ showed less ceiling effect. Conclusion The original CHAQ-38 with the "mean" score calculation method as well as the revised CHAQ are a possible alternative for future studies. However, there is a need for further prospective studies to improve the CHAQ and to support our findings.